Diversidade da dieta de morcegos frugívoros e a heterogeneidade da vegetação - Silva, Lilith Conceição (2019)
Tropical forests are highly diverse and provide resources for many animals, such as those that eat fruits and function as seed dispersers, helping with ecosystem maintain. Frugivory is one of the most common habits among neotropical bats and the diversity of frugivorous bats has been associated with a great abundance of resources. More heterogeneous environments may provide more resources, accommodating more species with different combinations of their uses, which may influence the number of plants consumed by bats. In this dissertation, we investigated the relationship between heterogeneity of vegetation and diet diversity of fruit bats. The diversity of diet was estimated using the Bootstrap method, Using the data from seed found on the feces of frugivore bats collected during 40 nights between the months of August 2017 and September 2018, in 10 mist networks in 10 forest fragments in the south of Minas Gerais. Data on arboreal vegetation was obtained by creating 10 plots for each fragment measuring 10 x 10 m each. Measurements were: tree diameter at breast height (DHB), tree height and canopy cover; tree species were identified. Within each plot, a 5 x 5m subplot was designated, and the same data were obtained for the vegetation under regeneration. The beta diversity of the structure was calculated for the arboreal vegetation and the vegetation under regeneration using the means of collected data, obtaining the mean distance of the centroid by fragment, and the values were compared by a permutation test. The arboreal vegetation β diversity and the vegetation under regeneration were obtained by using the abundance of each plant species per plot, finding the mean centroid distance per fragment and comparing the values using a permutation test. A principal component analysis was performed with the values of the three types of β diversity and the main axes were extracted. Generalized linear models (GLM) were constructed to relate the diversity of the diet to the species that consumed more seeds and mixed models (GLMM) to the community with the values of the diversities and with the main axes of the PCA. Of the 781 bats captured, 688 individuals from 10 species were frugivorous and 377 records were obtained from seeds of 31 plant species. The three species of bats with the highest number of seeds consumed were Carollia perspicillata, Sturnira lilium, and Artibeus lituratus. The species A. lituratus responded positively to the arboreal vegetation β diversity, C. perspicillata and the total species also responded positively to the same variable after removal from a discrepant point, S. lilium did not respond to any variable. For the models with axes of the PCA, only A. lituratus responded positively to axis 1. These results suggest that tree vegetation heterogeneity is an important factor for the diversity of the frugivore bats diet, however, the response may change according to the biology of the species. The results demonstrate that the loss of tree diversity may affect the ecosystem services promoted by these bats.